THE IMPACT OF CLIMATE CHANGE ON THE ECONOMIES OF AFRICAN COUNTRIES - Lar, Sohlam P.; Choji, Niri Martha; Michael, Uji Iordye; Kefas, David Demshark (FUDMA Journal of Sciences, 2026)
This study investigates the impact of climate change on economic growth in African countries using panel data from the year 2000–2022. the analysis applies Panel Autoregressive Distributed Lag (Panel ARDL) model with the Pooled Mean Group (PMG) estimator, to capture both short-run and long-run equilibrium relationships between economic growth and key climate-related variables, including carbon dioxide (CO₂) emissions, energy imports, and population growth. Prior to estimation, cross-sectional dependence and panel unit root tests were conducted, which confirmed the suitability of the Panel ARDL approach. The empirical findings indicates that CO₂ emissions and energy imports exert positive and statistically significant impacts on economic growth in the short run, reflecting that the emission and energy-intensive activities temporarily stimulate economic performance in African countries. On the other hand, in the long run, the effects of CO₂ emissions, energy imports, and population growth on economic growth are statistically insignificant, signifying that reliance on these factors does not translate into sustained economic growth over time. The error correction term is negative and highly significant, which implies rapid convergence to long-run stability following short-run shocks. These findings suggest that although climate-related factors may stimulate short-term economic growth, they are insufficient for achieving long-term sustainable growth. The study therefore, emphasizes the need for African countries to transition toward cleaner energy sources, strengthening climate adaptation measures, and promotes productivity enhancing investments to achieve sustainable economic development in African countries.
Keywords: carbon dioxide (CO₂) emissions; energy imports; and population growth